Растить человека: Записки психолога / Л. М. Зюбин - Зюбин Леонид Михайлович (Лениздат, 1988)
Экземпляры: (20190130) / Инвентарный номер: 20393 / Цена: 0.40 / Сис.шифр: 88.83 / Авт.знак: З-98 / ББК: 88.834.023